Investigation of 3D steel frames with a reduced beam section and various web-opening shapes under internal column loss - Ali Altheeb; Ibrahim M. H. Alshaikh; Aref A. Abadel; Moncef L. Nehdi; B.H. Abu Bakar (Journal of Asian Architecture and Building Engineering)
The sudden loss of columns due to abnormal loads demonstrates a remarkable example of a localized failure that might ultimately result in the progressive collapse of the complete steel-framed structures. In this study, finite element (FE) simulations are implemented by utilizing ABAQUS-Explicit to investigate the progressive collapse of two-storey steel reduced beam section (RBS) frames with web openings. The reliability and accuracy of the FE models are validated by comparing the obtained results with currently available experimental test results. A numerical investigation is conducted on twenty-eight RBS frames, each with a distinct web opening form (i.e. circular, square, and hexagon holes), different sizes of (D = 75, 90, and 105 mm), and varying distances of (25, 50, and 100 mm) from the center of the flange-reduced to the web opening. The failure modes, load-displacement characteristics, and development of catenary action are evaluated. The results showed that the specimens with square holes showed a greater degree of damage and lower load-carrying capacity compared with the specimens that have circle and hexagonal holes. In addition, an increased opening size resulted in a decrease in load-bearing capacity at small distances, thereby resulting in an increased capacity at a large distance.